Physiological value of stabilometric studies in complex coordination sports - Krasnoperova, T. V.; Kotelevskaya, N. B.; Abramova, T. V. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to theoretically ground and test benefits of a stabilometric model for complex coordination sports. Methods and structure of the study. Stabilometric platform makes it possible to rate the postural control movements in projection onto the horizontal plane; with the major persistent deviations being often indicative of the musculoskeletal system functionality disorders or the movement coordination system disorders. The stabilometric test data and analyses make it possible to effectively track such disorders and make the relevant corrections to the individual training systems.